Analysis of Challenges and Opportunities for Islamic Religious Education in the Era of Society 5.0 - Nurlaili; Novriyana, Yola; Qolbi Khoiri; Fitri Sulastri (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
Society 5.0 has brought many changes in the order of life, one of which is Islamic religious education. The aim of this research is to examine the impact of society 5.0 in the world of Islamic Religious Education in schools. The research method used is the literatus study, with previous research studies being the source of information. The results of this study are, there are several challenges that must be faced Islamic Religious Education in schools, among them are: 1) teachers and educational institutions must be able to ensure the credibility of science received by pupils outside school, 2) must be capable of explaining the good and bad impacts of technological developments to strengthen pupils from taking examples of things that are not good, 3) must be adaptable to existing technology developments, 4) environmental issues living; 5) advances in information technology; 6) convergence of science and technology; 7) economics based on the economy; 8) the rise of creative and cultural industries; 9) shift in global economic power; 10) the impact and influence of technology; and 11) transformation, investment, and quality of education. In addition to creating new challenges, the society of the era 5.0 also provided several opportunities for Islamic Religion Education in schools, among them are: 1) facilitating access to science for the education of Islamic religion, 2) making teachers have the opportunity to be creative in creating teaching equipment with existing technology, 3) learning resources are easily available, 4) improve the quality of the Islamic religious education, 4) Islamic education process is becoming easier to spread even to out-of-school environments, 5) get the chance to conduct training in improving Human Resources (SDM) in the use of technology, and 6) see and fulfill the needs of the community with learning Islamic Education in school.